2015
DOI: 10.1177/1062860614566445
|View full text |Cite
|
Sign up to set email alerts
|

Quality Improvement Education for Health Professionals

Abstract: Effective quality improvement (QI) education should improve patient care, but many curriculum studies do not include clinical measures. The research team evaluated the prevalence of QI curricula with clinical measures and their association with several curricular features. MEDLINE, Embase, CINAHL, and ERIC were searched through December 31, 2013. Study selection and data extraction were completed by pairs of reviewers. Of 99 included studies, 11% were randomized, and 53% evaluated clinically relevant measures;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 26 publications
0
51
0
2
Order By: Relevance
“…Secondly, the ultimate goal to improve Resubmission Version 2 14-03-17 patient care or services (Level 4) is challenging not only because of similar complexities shared with education but because of poor research design. Attempts to evaluate patient care in education studies have resorted to reporting Level 2 outcomes instead (Starr et al 2016). Our review identified one study which reported improvement in patient processes using pre/post methods, however, these simplistic measures assume causal linkage between educational intervention and outcome, discounting the importance of contextual factors in practice (Bates, 2004), which is instead the very antithesis of quality improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the ultimate goal to improve Resubmission Version 2 14-03-17 patient care or services (Level 4) is challenging not only because of similar complexities shared with education but because of poor research design. Attempts to evaluate patient care in education studies have resorted to reporting Level 2 outcomes instead (Starr et al 2016). Our review identified one study which reported improvement in patient processes using pre/post methods, however, these simplistic measures assume causal linkage between educational intervention and outcome, discounting the importance of contextual factors in practice (Bates, 2004), which is instead the very antithesis of quality improvement.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,7,[13][14][15][16] Curricular objectives were to (1) engage residents in interprofessional QI; (2) demonstrate residents' improved QI confidence and knowledge; (3) apply QI principles to residents' practices; and (4) create opportunities for resident scholarship in QI. While the curriculum incorporated some didactics, the emphasis was on skill development in the form of resident-led QI projects.…”
Section: Methodsmentioning
confidence: 99%
“…O formato de seis sessões, com periodicidade semanal de duas horas cada, totalizando 12 horas de programa, foi elaborado tendo em vista resultados de diferentes estudos avaliados em meta-análise, sobre intervenções psicológicas positivas, em formato grupal, aplicada para adultos acima de 35 anos (Sin & Lyubomirsky, 2009). O programa está apoiado em abordagens de Terapia Cognitivo Comportamental (tcc) (Knapp, 2004) para a promoção e educação para a saúde (Starr et al, 2015), e perspectivas da Psicologia Positiva (Seligman, 2002;Snyder & Lopes, 2009), como estratégia para alcançar um melhor estado de saúde. A seguir, são apresentadas resumidamente as sessões, objetivos, variáveis trabalhadas, assim como atividades e abordagens da tcc utilizadas em cada sessão e ao longo do programa.…”
Section: Descrição Da Intervenção: O Programa Vem Serunclassified